Socioeconomic position in early life, birth weight, childhood cognitive function, and adult mortality. A longitudinal study of Danish men born in 1953. Issue 9 (21st August 2003) - Osler, M; Andersen, A-M N; Due, P; Lund, R; Damsgaard, M T; Holstein, B E
Abstract : Objective: To examine the relation between socioeconomic position in early life and mortality in young adulthood, taking birth weight and childhood cognitive function into account. Design: A longitudinal study with record linkage to the Civil Registration System and Cause of Death Registry. The data were analysed using Cox regression. Setting: The metropolitan area of Copenhagen, Denmark. Subjects: 7493 male singletons born in 1953, who completed a questionnaire with various cognitive measures, in school at age 12 years, and for whom birth certificates with data on birth and parental characteristics had been traced manually in 1965. This population was followed up from April 1968 to January 2002 for information on mortality. Main outcome measures: Mortality from all causes, cardiovascular diseases, and violent deaths. Results: Men whose fathers were working class or of unknown social class at time of birth had higher mortality rates compared with those whose fathers were high/middle class: hazard ratio 1.39 (95% CI 1.15 to 1.67) and 2.04 (95% CI 1.48 to 2.83) respectively. Birth weight and childhood cognitive function were both related to father's social class and inversely associated with all cause mortality. The association between father's social class and mortality attenuated (HRworking class 1.30 (1.08 to 1.56); HRunkown class 1.81 (1.30 to 2.52)) after control for birth weight and cognitive function. Mortality from cardiovascular diseases and violent deaths was also significantly higher among men with fathers from the lower social classes. Conclusion: The inverse association between father's social class at time of birth and early adult mortality remains, however somewhat attenuated, after adjustment for birth weight and cognitive function.